At the heart itself of coloniality. Power, social totality and heterogeneity in the fisrt sociological works of Anibal Quijano (1962-1966) - Assis Clímaco, Danilo (2019)
The capacity of Anibal Quijano to remain as an influential author in the Latin American debate for over four decades does not obey a chameleonic style. Rather than a number of fundamentally solid axes from which he perceived and explored social transformations and intellectual debates. The article seeks to reveal some of the concepts that inhabit what Quijano once called “the epistemic heart itself of the idea of coloniality of power” (2013): power, social totality, and heterogeneity, these are already present in his first works. Thus becoming an extremely fertile method for exploring reality.